The linguistic nature of Children's scientific reasoning. (August 2019) - Van de Sande, E.; Kleemans, T.; Verhoeven, L.; Segers, E.
Highlights: Children's scientific reasoning skills were assessed in one coherent design. These skills were related to visuospatial and multiple linguistic abilities. Results indicated a three-component model of scientific reasoning skills. Linguistic abilities showed a major role over and above visuospatial abilities.